Estratégia de pequenas e médias empresas exportadoras do Rio Grande do Sul - Baumhardt, Jorge Alberto (Universidade do Vale do Rio do Sinos, 2008)
The present study focuses on the strategic thinking of exporting companies established on Rio Grande do Sul, and is the replication of Hermann Simon’s (1996) research about the German midsize successful companies. This research originated the book known as The Hidden Champions. It was developed a descriptive quantitative research in the form of survey was done with thirty-nine companies from various segments of activity. This research evaluated the strategic perception of companies within different views: goals and vision, elements of the external environment and elements of the internal environment. The model selected assesses the German companies, because of the success this country has on the international market. The results indicate that the internationalization of companies, is low with less than 30% of its revenue from exports, have an average local market share of 30.3%, and this allows 61.5% of them have some kind of influence on the local market. It was also observed differences in the strategies
Keywords: internacionalização; pequenas e médias empresas; estratégia; internationalization; small and medium enterprises; strategy; Ciências Sociais Aplicadas